Elucidating Spirocerca lupi spread in the Americas by using phylogenetic and phylogeographic analyses - Alfaro-Segura, Paula; Robleto-Quesada, Joby; Montenegro-Hidalgo, Víctor M.; Molina-Mora, Jose Arturo; Baneth, Gad; Verocai, Guilherme G.; Rodriguez-Vivas, Roger I.; Rojas, Alicia (Frontiers in Parasitology, 2023)
Spirocerca lupi is a parasitic nematode of domestic and wild canids of the world. This nematode induces esophageal spirocercosis and may eventually lead to carcinomas, aortic aneurisms, and death of the animal. Two genotypes of S. lupi have been described based on specimens from Europe, Asia, Africa, and Oceania, but no profound analysis has been conducted with S. lupi from the Americas. To study this, S. lupi specimens isolated from domestic dogs from Mexico, Costa Rica, and the United States, were molecularly characterized using 18S rDNA and cox1 fragments. Bayesian inference (BI) phylogenetic trees, Templeton-Crandall-Sing (TCS) haplotype networks and Principal coordinate analysis on nucleotide distances were constructed for each locus separately. In addition, a phylogeographic study using a fragment of the cox1 gene was used to infer the evolutionary history of the genus. BI cox1 trees grouped S. lupi from the Americas in genotype 1, together with Israeli specimens, and showed a high nucleotide identity with those worms. In the TCS network, American specimens clustered next to Israeli S. lupi. Furthermore, the 18S rDNA gene fragment separated Costa Rican worms from African, Asian, and European specimens and other species of the family Spiruridae. Interestingly, phylogeographic analysis suggested that the origin of S. vulpis was in Europe, and it later diverged into S. lupi that spread first to Africa, then to Asia and finally to the Americas. Therefore, we suggest that the worms from the American continent might have originated from Asia by dispersion of infected intermediate, paratenic or definitive hosts.